(untitled) (Scientific journal of the Fergana State University, 2025)
The article explores the theoretical and methodological foundations for developing higher education students’ axiological attitudes towards spiritual and cultural heritage, the methodological system for fostering these attitudes, and the effectiveness of such development. Additionally, it analyzes the social significance and educational characteristics of cultivating students’ axiological attitudes towards spiritual and cultural heritage.